Real-microcellular poly(ether-block-amide)/carbon fiber foams with improved mechanical property and surface quality for high-performance electromagnetic interference shielding applications - Wenli Li; Guoqun Zhao; Guilong Wang; Lei Zhang; Xinyang Li; Zhaorui Xu (Journal of Materials Research and Technology, 2023)
Challenges remain in large-scale and successive preparation of porous polymer composite component, which limits its practical applications for high-performance electromagnetic interference (EMI) shielding. Herein, a scalable and efficient method based on mold-opening foam injection molding was developed to fabricate carbon fiber (CF) reinforced polymer composite foams for EMI shielding applications. Thanks to the novel foaming process and heterogeneous nucleation effect of CF, real microcellular poly(ether-block-amide) (PEBA)/CF composite foams with an average cell size of 6.6 μm and a cell density of up to 109 cells/cm3 were achieved. Due to the significantly refined cellular morphology, the PEBA/CF composite foams exhibit superior EMI shielding performance over the unfoamed composites which was characterized by absorption-dominated shielding characteristics and significantly enhanced EMI shielding effectiveness. Furthermore, compared with the unfoamed case, the foamed PEBA/CF composites with refined cellular morphology shows greatly improved cold toughness and duality, and the tensile strain at break and specific tensile toughness are increased by 88.6% and 109.1%, respectively. Moreover, real-microcellular PEBA/CF composite foams have remarkably enhanced surface quality than those fabricated by regular foam injection molding process, and the surface roughness can be maximumly increased by 91.6%. Thus, this study provides a promising strategy for producing lightweight and strong components for high-performance EMI shielding applications.